THE THE EFFECT OF PERCEPTION OF BENEFITS, EASE OF USE, AND TRUST ON THE INTENTION TO CONTINUE TO USE QRIS : (CASE STUDY OF TICKET PURCHASE AT BALEKAMBANG PARK, SURAKARTA) - Muhammad Dimas Aji Prasetya; Kurniawati Darmaningrum; Atik Lusia (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the influence of perceived usefulness, ease of use, and trust on the intention to continue using QRIS in purchasing tourist tickets at Balekambang Park, Surakarta. Methods: The study used a quantitative approach with a survey method. Data were obtained by distributing questionnaires to respondents who had used QRIS to pay for tourist tickets. The data analysis technique used was multiple linear regression with the help of SPSS software. Results: The results showed that perceived usefulness, ease of use, and trust had a positive and significant effect on the intention to continue using QRIS, with effects that were simultaneous and partially independent. This finding indicates that the higher the perceived usefulness, ease of use, and level of user trust in QRIS, the greater the tendency of users to continue using QRIS in tourist ticket payment transactions. This research is expected to contribute to tourism destination managers and digital payment service providers in increasing the adoption and sustainability of QRIS use. Keywords: ease of use, perceived usefulness, trust, intention to continue using, QRIS